2021
DOI: 10.15586/aei.v49i5.458
|View full text |Cite
|
Sign up to set email alerts
|

MiR-216a-5p alleviates LPS-induced inflammation in the human bronchial epithelial cell by inhibition of TGF-β1 signaling via down-regulating TGFBR2

Abstract: Objective: Bronchopneumonia is a common respiratory infection disease and is the leading cause of hospitalization in children under 5 years of age. Inflammation is the primary response caused by bronchopneumonia. But the detailed underlying mechanism of inflammation in bronchopneumonia remains unclear. Therefore, this study focused on studying the effect of miR-216a-5p on inflammation induced by bronchopneumonia and investigate the potential mechanism underlying it.Methods: Human bronchial epithelial cells (BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Several studies have manifested that miRNAs can prevent or accelerate Diabetic kidney disease (DKD) progressions [ 2 , 3 ]. miR-216a-5p is a member of the miRNA family, can attenuate the process of various diseases, such as cancer [ 4 , 5 ], Alzheimer’s disease [ 6 ], bronchopneumonia [ 7 ], neuropathic pain [ 8 ], etc. Additionally, research indicated that miR-216a-5p could induce HG-induced EMT and fibrogenesis by BMP7 in DKD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have manifested that miRNAs can prevent or accelerate Diabetic kidney disease (DKD) progressions [ 2 , 3 ]. miR-216a-5p is a member of the miRNA family, can attenuate the process of various diseases, such as cancer [ 4 , 5 ], Alzheimer’s disease [ 6 ], bronchopneumonia [ 7 ], neuropathic pain [ 8 ], etc. Additionally, research indicated that miR-216a-5p could induce HG-induced EMT and fibrogenesis by BMP7 in DKD [ 9 ].…”
Section: Introductionmentioning
confidence: 99%